Pengaruh Motivasi Kerja, Lingkungan Kerja Fisik, Employee Engagement Terhadap Kinerja Perawat di Rumah Sakit Taman Harapan Baru - Rina Apulina br Ginting; Wahyuni SpEm; Reza Hilmy (Jurnal Health Sains, 2022)
Employee perfomance is an important parameter in health services. Increasing the productivity and perfomance of health workes is very important in an effort to increase the efficiency of health services. Nurse perfomance is strongly influenced by knowledge, skills, work motivation, physical work environment, and employee engagement. The aim of this study to analyze the effect of work motivation, physical work environment, and employee engagement on the perfomance of nurses at Taman Haran Baru Hospital. This study is using cross sectional method with total sample of  54 people.  The results of this study have a simultaneous effect between work motivation (p = 0.004), physical work environment (p=0.001), dan employee engagement (p=0.048) on nurse perfomance. Conclussion, Nurses at Taman Harapan Baru Hospital have high work motivation and employee engagement. While the physical work environment is still moderate value. Suggestion to the Taman Harapan Baru Hospital in order to improve the condition of the physical work environment, give appreciation to nurses to create a comfortable environment.